Pembelajaran Sifat-Sifat Grafik Fungsi Eksponen dan Logaritma dengan Software Geogebra - Rizka Azizatul Latifah (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
Mathematics teaching and learning is expected to raise 21st century skills called the 4C’s (critical thinking and problem solving, communication, collaboration, and creative and innovative). One of the activities to reach the mentioned skills is doing graph analysis. The characteristics of graph of exponential and logarithmic function is one of topics in which an analysis is needed. To analysis a graph, students need a right media. Geogebra is software that visualizes mathematics object including graphic function. This paper discusses the way how teach characteristics of graphs of exponential and logarithmic function using Geogebra.